Specific Peculiarities of Organizing Educational and Field Practice Through Information Technology - Ongarov Mansurbek Bayrambekovich (Miasto Przyszłości, 2024)
Information technologies in the process of conducting field practice, improving the effectiveness of pedagogical methods, changing the work of teachers, improving their working methods, the use of pedagogical systems during continuous field practice. This contributes to a simpler and more meaningful solution of specific tasks in the organization and management of pedagogical processes.